The First Day - Skrinar, Hannah (Skrinar, Hannah ; Pearse, Sally, 2008)
Verzio FF Submission Galina is a Roma girl from Slovakia whose family has sought asylum in Sheffield, UK on grounds of discrimination. This short film followes Galina's first day in a nursery where she will not be the only child who cannot speak English.